Challenges Adversely Affecting the Performance of the Manufacturing Sector of Developing Countries - Munkaila, Alhassan (International Journal of Engineering and Management Research, 2021)
The manufacturing sector of Ghana is bedeviled with many challenges, both external and internal, ranging from poor regulatory environment to inadequate level of skilled labour. Manufacturing firms in Ghana were surveyed, using a sample size of 120, based on purposive sampling. The study was poised to determine those variables that were available and those that were not available in the firms and were a setback. In addition a rating scale was used to determine those that were more critical and could adversely affect the performance of the sector. The results revealed there were high rent costs (84.2%) and influx of foreign products (87.5%) as well as inadequate level of skilled labour (77.5). The study was also intended to determine which variable was critically challenging and its absence could affect the performance of the sector. Clearly, poor regulatory environment was ranked the highest on the part of external challenges while inadequate skilled labour was rank the highest on the part of internal challenges. It is therefore recommended that skills development should be the priority of manufacturing firms, with the aim of closing manufacturing skills gap. Further, the government should make conscious attempt to regulate the influx of foreign products into the country.